Prokrastinasi Akademik dan Stres Akademik pada Siswa Kelas XI Khusus di SMAN 7 Wajo - Arni AR; A.Wahyuni; Yammar Yammar; Ikdafila Ikdafila; Nirmawati Darwis; Fitriani Fitriani (Journal Research of Nursing & Midwifery (JRNM), 2026)
Academic stress has become one of the most prevalent psychological problems among high school students due to increasing academic demands, including excessive assignments, examinations, academic competition, and expectations to achieve high academic performance. One behavioral factor that is considered to contribute to academic stress is academic procrastination, which refers to the intentional delay in initiating or completing academic tasks despite being aware of the potential negative consequences. This study aimed to examine the relationship between academic procrastination and academic stress among Grade XI special-class students at SMAN 7 Wajo. A quantitative analytical study employing a cross-sectional design was conducted among 35 students selected using a total sampling technique. Data were collected using the Ferrari Academic Procrastination Questionnaire and the Educational Stress Scale for Adolescents (ESSA). Statistical analysis was performed using Fisher's Exact Test with a significance level of 0.05. The results revealed a statistically significant relationship between academic procrastination and academic stress (p = 0.015), indicating that students with higher levels of academic procrastination were more likely to experience greater academic stress. These findings suggest that delaying academic tasks may increase psychological pressure through poor time management and the accumulation of academic workload. In conclusion, academic procrastination is significantly associated with academic stress among Grade XI special-class students at SMAN 7 Wajo. Schools are encouraged to develop intervention programs focusing on self-regulation, effective time management, and adaptive coping strategies to reduce procrastination and improve students' psychological well-being.